Profil Pengobatan Pasien Rawat Jalan Diabetes Melitus Tipe 2 setelah Pelaksanaan JKN - MITA RESTINIA; YUSI ANGGRIANI; TRI KUSUMAENI; ARIES MERYTA (Fakultas Farmasi Universitas Pancasila, 2015)
In 2014, health insurance entirely colected together into Badan Penyelenggara Jaminan Sosial (BPJS) became Jaminan Kesehatan Nasional (JKN). But there is different payment method that is ASKES used Fee for Services (FFS) method and BPJS use INA-CBGs method. Diabetes mellitus is a chronic disease that patients with that diagnosed should use drug continuously. Therefore, research with conducted by time series longitudinal retrospective method that aimed to observe impact of JKN about drug treatment profile among outpatients of type 2 DM in X Hospital Jakarta. Total of samples collected were 84 patients, 31 (36.90%) of male and 53 (63.10%) of female. Most patients (29.76%) were 66-70 years old. There were 38 patients with 10 times of visite, 27 patients with 11 times of visite, 19 patients with 12 times of visit. Based on drug treatment profile, after JKN has launched, decreasing of total of drug use, number of visit increased to 42 visits, kinds of drug appropriate with DPHO decreased until 79%, kinds of drug appropriate with national formularium rised 97%, generic drugs also increased 54% and non generic drug decreased 47%. Based on descriptive analysis, when JKN has launched, there were impact toward drug treatment profile.